PROSES PEMBUATAN MATA PISAU PENCACAH DAGING DENGAN MENGGUNAKAN METODE BUBUT MANUAL - FAHRIZA, MUHAMAD ILHAM; JANNATI, EIDELWEIS DEWI (Universitas Majalengka, 2025)
The metalworking process plays a crucial role in the production of machine components, particularly when using a lathe. Continuous innovation is essential to improve the quality of production outcomes. Various methods can be applied, such as selecting the appropriate cutting tool type, determining the depth of cut, and setting the correct spindle speed. The main issue lies in how variations in tool type, spindle speed, and cutting depth affect the surface texture and hardness of the work material during conventional turning operations. This study focuses on the design of a meat chopper blade and a direct examination of the stages involved in its manufacturing process using a manual lathe. The methodology employed to collect data in this research includes systematic observation of the subject to directly ensure the planned investigation, followed by interviews involving direct question-and-answer sessions with technicians and factory managers, as well as a literature review that requires gathering information from relevant books and online resources. The purpose of the meat chopper blade manufacturing procedure is to identify the material used, ensure the proper tools and machines are applied, and describe each stage of the blade-making process. The manufacturing process involves preparing the materials, carrying out cutting procedures, performing turning operations, conducting milling activities, executing drilling processes, applying hardening treatment, and completing finishing operations.In this study, the meat chopper blade is manufactured using ST 37 steel. The process begins with material selection, followed by manual turning, rough turning, finishing turning, center hole boring, deep turning, drilling on four sides, and surface turning. The process continues with blade shaping using a grinding machine to remove excess material, and concludes with the final finishing stage, which includes grinding and polishing.